Science Investigation Through Student Worksheet in Environmental Pollution Material to Support SDGs “Clean Water and Sanitation” - Marisa Christina Tapilouw; Farida Zuraina Mohd Yusof (Jurnal Pendidikan Sains Indonesia, 2026)
Science learning plays an important role in raising students’ environmental awareness, which begins in young people. The focus of this study is the implementation of a student worksheet in a science learning activity. The purposes of this study are (1) to design questions in student worksheets about environmental pollution, and (2) to analyze students’ science investigations as a response to the science learning activity. This research is in support of SDGs clean water and sanitation. This study is a descriptive study with a qualitative approach.  In order to answer problems, the descriptive research describes the existing situation with a scientific procedure. The subject of this study was 36 student class 7 and 32 student class 10. These student worksheets (Class 7 and Class 10) were implemented in science learning by observing river pollution. In class 7 and class 10, the result showed that food waste polluted the river. Most group in class 7 gave solution that we have to raise environmental awareness. In the other band, most group in class 10 observed that industrial and domestic activities cause river pollution. The class 7 student responded to the question in detail because of direct observation. Meanwhile, the class 10 student responded to the question limited by observation through indirect observation. For conclusion, (1) the student worksheets were valid and implemented in science investigation; (2) from student’s observation, Waste resulting from human activities in rivers causes rivers to be polluted and disrupts the balance of the ecosystem